The one and only Marigold - Heide, Florence Parry (Schwartz & Wade Books, 2009)
Relates the misadventures of Marigold, who does not agree with anyone, as she shops with her mother for a coat, becomes interested in a new hobby, finds a way to "bug" her best friend, Maxine, and imaginatively copes with finding the right outfit for the first day of school.